Multifunctional Janus metasurfaces achieving arbitrary wavefront manipulation at dual frequency. (November 2022) - Tang, Ziyi; Li, Ling; Zhang, Haochen; Yang, Jianing; Hu, Jie; Lu, Xuehua; Hu, Yongqiang; Qi, Song; Liu, Ke; Tian, Mingyang; Jin, Jinjin; Zhang, Zuojun; et al.
Graphical abstract: Highlights: The dual frequency metasurface that breaks out-of-plane symmetry is proposed to realizes phase and direction multiplexing. The unit cells exhibit high working efficiencies that the average cross-polarized transmissive amplitudes are larger than 0.86. The Janus dual frequency meta-device could generate asymmetric holograms for information encryption/decryption. Abstract: Metasurface with simultaneous control of amplitude, phase, and polarization of electromagnetic (EM) waves has drawn great attention in modern optics and photonics. However, conventional metasurfaces are mainly designed for single frequency and functionality. Here, we proposed a simple yet powerful methodology for the design of a dual-frequency multifunctional Janus metasurface. The designed transmissive device with sub-wavelength thickness is not only able to achieve completely independent phase modulation at two preset frequencies, but can also realize efficient asymmetric transmission of EM waves. On the other hand, the out-of-plane symmetry breaking also enables the realization of different functions for opposite propagation directions. As a proof of concept, a Janus beam deflector and a Janus metalens with direction- and frequency-controlled functionalities are demonstrated numerically. A dual-frequency Janus metasurface for direction-dependent meta-holograms is validated both numerically and experimentally. Therefore, we believe the proposed metasurfaces with direction- and frequency-dependent versatile functionalities may have great potential in the fields such as polarization manipulation, chiral sensing and information encryption.